Silencing CDK6-AS1 inhibits LPS-induced inflammatory damage in HK-2 cells - Wu Ling (De Gruyter, 2021)
In this study, we aim to discover the importance of long non-coding RNA cyclin-dependent kinase 6 (CDK6)-AS1 in lipopolysaccharide (LPS)-induced HK-2 cells. We treated the HK-2 cells with LPS and knocked down CDK6-AS1 in HK-2 cells and then analyzed the effects of CDK6-AS1 on the viability of cell, cell apoptosis, the expression of cytokines via MTT, flow cytometry, enzyme-linked immunosorbent assay (ELISA), and qPCR. The results showed that silencing CDK6-AS1 alleviated LPS-induced inhibition of HK-2 cell proliferation, release of IL-1β, IL-8, IL-6, and TNF-α, cell apoptosis, and decrease in mitochondrial membrane potential. In addition, decreasing the level of CDK6-AS1 inhibited the reduction of Bcl-2 levels, the expression of Bax, cleaved caspade-9, and cleaved caspase-3, induced by LPS. In conclusion, lowering CDK6-AS1 level alleviates LPS-induced inflammatory damage in HK-2 cells.